Development of Mobile Application-Based Learning Media to Support Students' Mathematical Communication in Geometric Transformation - Annisaq Ardies; Budi Murtiyasa (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
Habituation in the use of communication in the realm of learning is very necessary and also needs further attention regarding its implementation. However, intermediate-level students still have difficulties composing scientific arguments. This study aims to develop mobile application-based learning media and determine the effect of learning media on improving students' mathematical communication skills. This research uses the Research and Development (R&D) method and the ADDIE model with five stages. The results of the validation by material experts and media experts obtained results in the very feasible category, and the results of the pre-test and post-test showed that there was a significant effect on the level of mathematical communication skills after using the “Cek Kommat” application. The results of the student questionnaire obtained fall into the feasible category for the software aspect and the very feasible category for the learning aspect and visual communication. Thus, the product is suitable for use by students and is able to provide significant results in improving mathematical communication skills in students.